Nonlinear Triangular Intuitionistic Fuzzy Number and Its Application in Linear Integral Equation. (3rd March 2019) - Mondal, Sankar Prasad; Goswami, Adrijit; Kumar De, Sujit
Abstract : In this paper we introduce the different arithmetic operations on nonlinear intuitionistic fuzzy number (NIFN). All the arithmetic operations are done by max-min principle method which is nothing but the application of interval analysis. We also define the nonlinear intuitionistic fuzzy function which is used for finding the values, ambiguities, and ranking of nonlinear intuitionistic fuzzy number. The de-i-fuzzification of the corresponding intuitionistic fuzzy solution is done by average of( α, β ) -cut method. Finally we solve integral equation with NIFN by the help of intuitionistic fuzzy Laplace transform method.